Ethnoecology of pollination and pollinators - Marie Roué; Vincent Battesti; Nicolas Césard; Romain Simenel (Revue d'ethnoécologie)
This paper brings together three case studies on the interrelationships amongst people, pollination processes and pollinators (notably honeybees). In the palm groves of Saharan oases, the milieu and varieties of palm trees are created by horticulturalists, who fulfil themselves the role of pollinators. In southern Morocco, entire landscapes, including in particular the agroforests of argan trees, are the products of a remarkable symbiosis between bees and people. In Indonesia, honey harvesters have an exacting local knowledge of the giant honeybees and the timing and nature of blooms. They use this knowledge to attract migratory swarms and to decide the optimal moment to harvest honey so that the bees are incited to return.The authors, specialists in social system/ecosystem interactions, decided to pool their expertise so as to render more accessible their research results, which are often dispersed amongst journals specialized in different cultural areas. By focusing their analyses instead on an important biological phenomenon threatened by human action (in this case, pollination), they hope that their audience will also include biologists, policy makers and environmental managers. Given the growing diversity and complexity of threats facing biodiversity, the responses proposed by conservation biology alone are often inadequate. To understand the dynamics of anthropo-ecosystems, the outcomes of a long co-evolutionary process involving a wide range of living beings, an interdisciplinary approach is mandatory. Conservation and sustainable use cannot be achieved without an understanding of local people's knowledge and practices, a prerequisite for establishing in partnership with them, protection measures that are both respectful and locally adapted.